Atención integral al adulto mayor en la Comunidad Monseñor Romero - Orellana Chacón, Esmeralda Lisbeth; Tejada Tobar, Rafael Alexander; Cerón Velasco, Angela Yamileth (Universidad de El Salvador. Facultad de Ciencias y Humanidades., 2025)
Disponible en soporte impreso